Effects of using problem-solving guide and explanatory support in program visualization tool on reducing students’ misconceptions in learning data structure concepts - Mtaho, Adam B (Bulletin of Social Informatics Theory and Application, 2023)
The tendency of novice programmers to hold misconceptions when learning data structures is one of the challenges that novice programmers face in computer science education. Holding misconceptions can result in students’ demotivation and high failure rates in learning the subject. This article presents the findings of an experimental study that was conducted to determine whether using the CeliotM Program visualization tool could help students learn CS 122 (data structures) at the College of Informatics and Virtual Education of the University of Dodoma with fewer misconceptions. The design chosen was a single factor between the experiment designs, with the number of errors committed by the students when writing programs as a dependent variable. The experimental group received instruction using the teaching technique employed by CeliotM, while the control group received instruction using the conventional lecture method. Results show that the use of CeliotM significantly reduced students misconceptions compared to the conventional lecture method. The study's important findings suggest that employing the CeliotM framework can help students understand data structures more effectively by minimizing their misconceptions and hence enhance their programming competencies.